HUBUNGAN HUKUM ANTARA DRIVER DENGAN PERUSAHAAN BERBASIS APLIKASI STUDI PERBANDINGAN NEGARA INDONESIA DENGAN NEGARA BAGIAN CALIFORNIA AMERIKA SERIKAT - Resky Pradhana Romli (Jurnal Perspektif Hukum, 2022)
PT Applications Karya Anak Bangsa (Gojek) is a Limited Liability Company with a license as a technology company to provide applications but the online motorcycle taxi application is used for transportation services whose regulations for online transportation do not have strong legal certainty. Application companies are not required to provide "workers' rights" to driver partners such as overtime pay, job security, or severance pay if the partnership ends, insurance, and paid leave at the same time the State of California has passed a rule called Assembly Bill 5 where the California State government changed Definition of Partner which basically means that if an employee works regularly for a company and his job is an undeniable part of the company, the employee must be appointed as a permanent employee. The purpose of this study is to find out how the legal relationship between application-based companies and drivers in Indonesia compares. The research approach used is a conceptual and comparative legal approach that uses primary, secondary and tertiary legal materials where data collection techniques are carried out through literature studies and then analyzed using qualitative methods.This study concludes that the difference in the legal relationship between application-based companies and driver partners is due to differences in the legal system where the State of Indonesia adheres to Civil Law tends to take longer to respond to developments in society and the United States which adheres to Common Law where the Judge's Decision as a source of law in the Common Law system can respond quickly to changes in society.